GAMBARAN PENGETAHUAN DAN KEPATUHAN IBU HAMIL TENTANG PEMERIKSAAN TRIPLE ELIMINASI DI PUSKESMAS NAMLEA - ASIYAH, SITI; Widiastuti, Wuri (STIKES dan AKZI Karya Husada Kediri, 2025)
The benefits of triple elimination examination are for early detection of HIV, Syphilis and Hepatitis B viruses which can recognize signs, characteristics and risks of threats as quickly as possible. Early detection, screening or health screening of pregnant women is carried out during integrated antenatal care so that they are able to undergo a healthy pregnancy and delivery. The aim of this research is to determine the description of knowledge and compliance of pregnant women regarding triple elimination examinations at the Namlea Community Health Center in 2024. The research design used was descriptive, the location of this research was carried out at the Namlea Community Health Center, Buru Regency. The variable in this study, namely the single variable, is the knowledge and compliance of pregnant women regarding the triple elimination examination. The population in this study was all pregnant women in the Namlea Public Health Center working area, Buru Regency, from an estimated August 2024 total of 30 respondents. The sampling technique used was total sampling. The research was conducted on 12-22 August 2024. The research instrument used was a questionnaire, and data analysis started from editing, scoring and tabulating. The results of research on Pregnant Women's Knowledge of Triple Elimination Examinations at the Namlea Community Health Center mostly had insufficient knowledge, namely 22 respondents (73.3%), while the researchers' analysis data related to the compliance of pregnant women regarding Triple Elimination Examinations of most respondents. 22 respondents (73.3%) did not comply with the triple elimination examination. The research results are in line with theory and previous research results, where the better the knowledge of pregnant women, the better the mother's compliance in carrying out triple elimination examinations during pregnancy.